EFFECTIVENESS OF ONE DAY PROMO IN INCREASING SALES OF NPK FERTILIZER PRODUCTS 30-6-8 IN PT. XYZ - Ellin Permatasari; Citra Savitri; Syifa Pramudita Faddila (Jurnal Mantik, 2022)
The presence of the national fertilizer industry can not only make a significant contribution to the development of the agricultural sector, but also has an impact on the development of other sectors, such as the chemical industry and other service industries. PT. XYZ is a subsidiary of PT. Pupuk Indonesia Holding Company which is engaged in the national fertilizer industry. The NPK 30-6-8 product is a product of the Retail Sales Department at PT. XYZ. Recently, the Retail Sales department carried out a promotional activity called One Day Promo (ODP) for NPK 30-6-8 products. The purpose of this study was to examine the evaluation of the implementation of the One Day Promo carried out by the Retail Sales department in increasing sales of NPK 30-6-8 products. The method used in this research is a descriptive approach and data collection techniques are carried out by means of observation and interviews. The results showed that the implementation of the One Day Promo (ODP) could not be said to be effective because the results of the activity only increased by 5% and after the activity the sales again decreased drastically. In addition, it was found that the factors causing the decline in sales after ODP were carried out were due to an increase in the price of fertilizer production, causing product prices to rise, limited stock availability, low selling power of farmers, low application of these products to farmers, and the absence of budget support.